Моделювання полегшеного тампонажного каменю з домішкою цеолітового борошна - Орловський, Віталій Миколайович; Кузьмичев, Богдан В. (Національний технічний університет "Харківський політехнічний інститут", 2023)
The purpose of this work is to obtain a statistical mathematical model of a modified lightweight tamponage stone with a lightweight admixture – finely dispersed zeolite powder (flour) with a response function - stone strength. In particular, the task is to establish the effect of the modifying admixture - zeolite flour on the strength of the tamponade stone. Method. A rotatable central composition experiment plan was used to create a statistical model. The obtained results were processed using the method of computer mathematical modeling using the program STATGRAPHICS Plus for Windows. The results. A modified lightweight tamponage material with a lightweight admixture - finely dispersed zeolite flour was created and studied. A statistical mathematical model of stone strength based on lightweight tamponage material was obtained, depending on the content of components in the mixture and hardening conditions. The resulting mathematical model can be used for engineering evaluations of the influence of factors on the strength of cement stone and is fully confirmed by the physical and chemical processes that occur during hardening of the tamponage solution. Scientific novelty. The scientific value of this work lies in the fact that the selection of optimal recipes of the new modified lightweight tamponage material, intended for use in difficult mining and geological conditions of oil and gas wells, was carried out. Practical significance. The results of the work have practical application in the cementing of deep wells in oil and gas fields and geological exploration areas in difficult mining and geological conditions of oil and gas fields of Ukraine.

Метою даної роботи є одержання статистичної математичної моделі модифікованого полегшеного тампонажного каменю з полегшувальною домішкою − онкодисперсним цеолітовим порошком (борошном) з функцією відгуку – міцність каменю. Зокрема, ставиться задача встановлення впливу на міцність тампонажного каменю модифікуючої домішки − цеолітового борошна. Методика. Для створення статистичної моделі був використаний ротатабельний центральнокомпозиційний план експерименту. Отримані результати були оброблені за допомогою методу комп'ютерного математичного моделювання, використовуючи програму STATGRAPHICS Plus for Windows. Результати. Створено і досліджено модифікований полегшений тампонажний матеріал з полегшувальною домішкою − онкодисперсним цеолітовим борошном. Одержано статистичну математичну модель міцності каменю на основі полегшеного тампонажного матеріалу залежно від вмісту компонентів у суміші та умов тужавіння. Отримана математична модель може бути використана для інженерних оцінок впливу факторів на міцність цементного каменю і повністю підтверджується фізико-хімічними процесами, що відбуваються при тужавінні тампонажного розчину. Наукова новизна. Наукова цінність даної праці полягає в тому, що проведено підбір раціональних рецептур нового модифікованого полегшеного тампонажного матеріалу, призначеного для застосування у складних гірничо-геологічних умовах нафтових і газових свердловин. Практична значимість. Результати роботи мають практичне застосування при цементуванні глибоких свердловин на нафтових і газових родовищах та геологорозвідувальних площах в складних гірничо-геологічних умовах нафтогазових родовищ України.
Simulation of Lightweight Tamponage Stone with Zeolith Flour Impurity
Keywords: well cementing; lightened tamponage material; lightweight admixture; strength of cement stone; modeling of lightened backfill stone; цементування свердловин; полегшені тампонажні матеріали; полегшувальні домішки; міцність цементного каменю; моделювання полегшеного тампонажного каменю